Given
4x - y = 20
2x + y = 22
Using the addition method, align like variables and constant, then, add them together
4x - y = 20
+ 2x + y = 22
6x + 0y = 42
6x = 42
Divide both sides by 6, to get rid of the coefficient on the left side
6x/6 = 42/6
x = 7
Now that we have x = 7, substitute it to any of the two given equations, in this case we will use 2x + y = 22 (note: using 4x - y = 20 works just as well)
2x + y = 22
2(7) + y = 22
14 + y = 22
y = 22 - 14
y = 8
Therefore, the solution to the system is (7,8).